Effect of Performance Appraisal, Supervisory Relationship and Employee Compensation on Employee Motivation in Nepalese Insurance Companies - Bohara, Sanju; Silwal, Zenith (Nepalese Journal of Finance, 2025)
This study examines the effect of performance appraisal, supervisory relationship and employee compensation on employee motivation in Nepalese insurance companies. Employee motivation is the dependent variable. The selected independent variables are performance appraisal, employee compensation, supervisor relationship, employee recognition, professional growth, and job security. The primary source of data is used to assess the opinions of the respondents regarding performance appraisal, employee compensation, supervisor relationship, employee recognition, professional growth, job security, and employee motivation. The study is based on primary data of 118 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of performance appraisal, supervisory relationship and employee compensation on employee motivation in Nepalese insurance companies. The study showed that performance appraisal has a positive impact on employee motivation. It indicates that fairness mechanism of performance appraisal leads to increase in employee motivation. Similarly, employee compensation has a positive impact on employee motivation. It indicates that higher the employee compensation, higher would be the employee motivation. Likewise, supervisor relationship has a positive impact on employee motivation. It indicates that healthy relationship with supervisor leads to increase in employee motivation. In addition, employee recognition has a positive impact on employee motivation. It indicates that better employee recognition mechanism leads to increase in employee motivation. Further, professional growth has a positive impact on employee motivation. It indicates that higher the professional growth, higher would be the employee motivation. In addition, job security has a positive impact on employee motivation. It indicates that higher the job security, higher would be the employee motivation.